2011 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE 2011) 2011
DOI: 10.1109/fuzzy.2011.6007518
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intuitionistic fuzzy similarity measures

Abstract: Numerous similarity measures between intuitionistic fuzzy sets are proposed in literature using different approaches. In this paper, relationship between some existing intuitionistic fuzzy similarity and distance measures are investigated. These relations are paramount for the choice of a similarity or a distance measure and its application for any research topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A comparative analysis by Li et al [29] shows the problems found in some IFSMs from literature, and the relationship between some IFSMs are done in Ref. [10].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis by Li et al [29] shows the problems found in some IFSMs from literature, and the relationship between some IFSMs are done in Ref. [10].…”
Section: Introductionmentioning
confidence: 99%